Autumn eaudiobook Seasonal quartet series, book 1. - Smith, Ali (Seasonal, 2017)
The first novel in Ali Smith's Seasonal Quartet is an unforgettable story about aging and time and love—and stories themselves. Autumn. Season of mists and mellow fruitfulness. Two old friends—Daniel, a centenarian, and Elisabeth, born in 1984—look to both the future and the past as the United Kingdom stands divided by a historic, once-in-a-generation summer. Love is won, love is lost. Hope is hand-in-hand with hopelessness. The seasons roll round, as ever. A luminous meditation on the meaning of richness and harvest and worth, Autumn is the first installment of Ali Smith's Seasonal Quartet, and it casts an eye over our own time: Who are we? What are we made of? Shakespearean jeu d'esprit, Keatsian melancholy, the sheer bright energy of 1960s pop art. Autumn is wide-ranging in time-scale and light-footed through histories. "Beautiful, subtle. ... Brimming with humanity and bending, despite everything, toward hope."—New York Times Book Review MAN BOOKER PRIZE FINALIST A Washington Post Notable Book One of the Best Books of the Year: NPR, The New York Times, Martha Kearney/The Guardian, Slate, Chicago Tribune, Southern Living, Milwaukee Journal-Sentinel, The Morning News, Kirkus Reviews Long-listed for the Gordon Burn Prize